Effective security management. - Sennewald, Charles A., 1931-; Baillie, Curtis (Butterworth-Heinemann, 2020)
Effective Security Management, Seventh Edition teaches practicing security professionals how to build their careers by mastering the fundamentals of good management. Charles Sennewald and Curtis Baillie bring common sense, wisdom and humor to this bestselling introduction to security management. For both new and experienced security managers, this resource is the classic book on the topic.